Combined cooling and water production using an adsorption-based system - Neo, Jocelyn Hui Yuan (2014)
Desalination process serves as a solution to address the issue regarding the world’s shortage of fresh water. However, for conventional desalination methods, a common drawback will be its intensive energy consumption. Furthermore, as chemicals will be used during the pre- and post-treatment of water, it will result in pollution when the waste discharges are released into the environment. Hence, an adsorption – desalination system serves as an alternative, whereby it makes use of waste heat to operate and thus minimises the utilisation of our limited energy resources. This report will begin by introducing the driving force for this project and its past literature research, followed by the introduction to the theory, experimental set-up and procedures, which will provide some insight to the working of the two-bed adsorption – desalination system. Subsequently, the discussion will focus on the review on all the duties took up by the author during the course of her project, such as her contributions before the set –up of the prototype, during the set –up of the prototype and during the conducting of experiments. It will also cover the details of the project, highlighting some of the author’s key results and findings during the experiment done. For this project, about 5°C of cooling and 113 ml of water were achieved after a cycle. In addition, comparisons of cooling effectiveness, chilled water temperature difference and water production effectiveness of the system under different working conditions (preheating/ precooling time) were done as well. Lastly, a review of the current system such as some of the problems faced during the experiment and their possible reasons will be discussed, followed by some recommendations for future work.